2016
DOI: 10.3892/or.2016.5300
|View full text |Cite
|
Sign up to set email alerts
|

Chemoradiotherapy and concurrent radiofrequency thermal therapy to treat primary rectal cancer and prediction of treatment responses

Abstract: The present study aimed to evaluate a previously reported predictive formula of output-limiting symptoms induced by radiofrequency (RF) to determine the efficacy of this neoadjuvant chemoradiation (NACR) and concurrent RF thermal therapy. The present study included 81 consecutive patients with confirmed diagnoses of rectal adenocarcinoma that was localized in the mid-low rectum (up to 12 cm from the anal verge) who received NACR [intensity-modulated radiotherapy (IMRT), 50 Gy/25 fractions, capecitabine 1,700 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“… 26 Second, liposomal formulations such as DHL have been shown to circulate in the blood for an extended period and erupt due to the enhanced permeability retention (EPR) effect, which ensures that the formulation remains in the tumor for as long as possible. 16 , 27 The delivery system of the tumor-feeding artery can increase intratumoral drug concentration. Meanwhile, heat in the tumor area after ablation can further induce the release of chemotherapeutic drugs.…”
Section: Discussionmentioning
confidence: 99%
“… 26 Second, liposomal formulations such as DHL have been shown to circulate in the blood for an extended period and erupt due to the enhanced permeability retention (EPR) effect, which ensures that the formulation remains in the tumor for as long as possible. 16 , 27 The delivery system of the tumor-feeding artery can increase intratumoral drug concentration. Meanwhile, heat in the tumor area after ablation can further induce the release of chemotherapeutic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated the efficacy of hyperthermia in treating breast cancer [ 24 26 ]. Furthermore, some reports have demonstrated the efficacy of RF hyperthermia for advanced cancer concomitant with chemotherapy and chemoradiotherapy [ 27 , 28 ]. Similarly, we applied 8 MHz RF hyperthermia equipment introduced in our hospital in October 2019 in combination with chemotherapy, and the patients received the combination therapy without major adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, radiofrequency hyperthermia (RHT) has widely been used as adjuvant therapy combined with chemotherapy or radiotherapy [17,18]. Until now, however, most animal studies used a water bath as a heat source due to difficulty in obtaining proper heating instruments for use in small animals [19,20,21,22,23].…”
Section: Discussionmentioning
confidence: 99%